If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3y + -2 = 5 Reorder the terms: -2 + 2x + 3y = 5 Solving -2 + 2x + 3y = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2x + 2 + 3y = 5 + 2 Reorder the terms: -2 + 2 + 2x + 3y = 5 + 2 Combine like terms: -2 + 2 = 0 0 + 2x + 3y = 5 + 2 2x + 3y = 5 + 2 Combine like terms: 5 + 2 = 7 2x + 3y = 7 Add '-3y' to each side of the equation. 2x + 3y + -3y = 7 + -3y Combine like terms: 3y + -3y = 0 2x + 0 = 7 + -3y 2x = 7 + -3y Divide each side by '2'. x = 3.5 + -1.5y Simplifying x = 3.5 + -1.5y
| -15=b-16 | | (2c-9)(c-1)=0 | | 31.25/25= | | 16x^2-36=-72 | | 2(x-7)+5=-9 | | 6s^4t^3-12s^3t^4=0 | | n(n-9)=0 | | 6x+7yx+9y=0 | | y^2+y-112=0 | | j(j-8)=0 | | 25/31.25= | | -9m=18 | | 4m(m-8)=0 | | 6=-4y+18 | | b^5+10b^4=0 | | 1/4x-2/5=5/6 | | (w-8)(3w+7)=0 | | 4-(2x+3)=5x-8 | | 1=v-8 | | -5-4r=-(1-2r) | | -9=2+p | | 8x-(5-x)+2(3x-4)=2 | | 3x^2=-18 | | 3r-4=5(r-1) | | 3k=45 | | 2(7/2)+y=11 | | 3(x-2)=-31+4x | | 8m+m-m-3m+2m=14 | | 3(2x+5)-5= | | 19s-13s-6s+s=19 | | 8.8=m-14.4 | | 7x+2y=94 |